Perilaku Investor Saham Individual Dalam Pengambilan Keputusan Investasi: Studi Hermeneutika-Kritis - Bayu Aprillianto; Novi Wulandari; Taufik Kurrohman (e-Journal Ekonomi Bisnis dan Akuntansi, 2014)
Investment decision making is a complex and vital process in investment. Investment decision was influenced by many factors. Accounting information as one of them, also has theoritically value relevance for investor in investment decision. This study aimed to know and analize the reality or practice of accounting information usage by individual stock investors in Indonesia Stock Exchange (BEI). This study used critic-hermeneutic study approach. Hermeneutic was used for interpretation of text which told by individual stock investors in the interview. There were 8 informant were interviewed in this study, who had different backgrounds i.e brokers, entrepreneurs, and college students. This result showed that accounting information as usefull value for investors, actually didn’t entirely used by individual stock investors, especially for investors who used technical analysis and another non-fundamental analysis in their stock analysis. Investor’s sophistication in acoounting information analysis (naive investor) also influenced the investor, so they didn’t analize accounting information. When accounting information didn’t influence to the investment decision of investor, no-effect hypothesis was applied. Whereas sophisticated investor who had sophistication in accounting information analysis, considered accounting information in their investment decision. When accounting information influenced to the investment decision of investor, mechanistic hypothesis was applied.